Antimicrobial effect of Methanol and Ethanol Extracts of Kembang Bulan (Tithonia diversifolia) Leaves against Staphylococcus aureus - Plumeriastuti, Hani; Habibi, Muhammad Afif; Tehupuring, Benjamin Christoffel; Effendi, Mustofa Helmi; Estoepangestie, Agnes Theresia Soelih; Sarudji, Suryanie; Witaningrum, Adiana Mutamsari (Media Kedokteran Hewan, 2021)
The purpose of this study was to determine how Staphylococcus aureus responded to Kembang Bulan (Tithonia diversifolia) leaf extract's antibacterial properties. Eight S. aureus bacterial isolates from three Surabaya dairy farms were used in this study. Tithonia diversifolia leaf extract at concentrations of 10%, 5%, 2.5%, 1.25%, and 0% were employed in the study's samples. The antibacterial activity of Tithonia diversifolia leaf extract was assessed in this work using the disk diffusion method and an inhibition zone estimated in millimeters. Based on the findings of this study, it was determined that Tithonia diversifolia leaf extract at 5% and 10% concentrations had 100% antibacterial activity against S. aureus in eight samples. As with S. aureus, Tithonia diversifolia leaf extract at concentrations of 0%, 1.25%, and 2.5% did not exhibit any antibacterial action.